AgGaSiSe4: Growth, crystal and band electronic structure, optoelectronic and piezoelectric properties. (November 2017) - Krymus, A.S.; Kityk, I.V.; Demchenko, P.; Parasyuk, O.V.; Myronchuk, G.L.; Khyzhun, O.Y.; Piasecki, M.
Graphical abstract: Highlights: Crystal AgGaSiSe4 was grown and its structure was determined. Electronic structure and chemical bonding of the AgGaSiSe4 crystal were examined by XPS and XES methods. Absorption coefficient in the temperature range 100–300 K was investigated. Temperature band gap variation coefficient and activation energies of dark conductivity were evaluated. IR transmission curve and the relaxation kinetics of photoinduced piezoelectric module were described. Abstract: Growth of AgGaSiSe4 single crystals, determination of their crystal structure, studies of electronic structure and optical properties are presented. The X-ray photoelectron core-level and valence-band spectra were measured. We recorded the X-ray emission Se Kβ2 and Ga Kβ2 bands, giving information on the energy distribution of the Se4p and Ga4p states, respectively, and compared with the X-ray photoelectron valence-band spectrum. The main contributions of the Se4p and Ga4p states have been found in the upper and central parts of the valence band, respectively, with their substantive contributions in other parts of the band. The spectral distribution of the absorption coefficient in the temperature range 100–300 K was investigated and band gap variation coefficient was evaluated (d Eg /d T = −4.5 × 10 −4 eV/K). The activation energies of dark conductivity were calculated as follows: Ea1 = 0.03 eV, Ea2 = 0.24 eV. The IR transmission curve and the relaxation kinetics of photoinduced piezoelectric module were described.